2011
DOI: 10.1136/pgmj.2011.117507
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia in rheumatoid arthritis: can we afford to ignore it?

Abstract: INTRODUCTION Anaemia is common in rheumatoid arthritis (RA). Clinicians may focus on rheumatological issues and assume anaemia of chronic disease (ACD). This study challenged this assumption and investigated the causes of anaemia in a large cohort of RA patients to assess its implications. METHODS The hospital where the study was conducted monitors regular full blood count and erythrocyte sedimentation rate (ESR) monthly in all RA patients on disease modifying drugs to assess efficacy and safety. A computerise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 35 publications
(20 reference statements)
1
18
1
3
Order By: Relevance
“…The Hb concentration in the COMBI anemia patients (97.39±5.03 g/l) was lower than in the IDA (100.51±5.43 g/l) and ACD groups (103.47±5.54 g/l), whereas the color index level and mean erythrocyte volume were lower in the IDA patients (0.68±0.06; 5.96±0.24 mcm 3 ) than in the ACD (0.92±0.04; 7.73±0.23 mcm 3 ) and COMBI groups (0.72±0.06; 6.38±0.83 mcm 3 ) (Table 1). Additionally, the TIBC in the IDA patients (79.34±3.02 mmol/l) showed a propensity toward increased values compared with the ACD group (52.27±5.36 mmol/l), but no statistically significant differences were noted between the IDA and COMBI (67.34±15.53 mmol/l) patients.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The Hb concentration in the COMBI anemia patients (97.39±5.03 g/l) was lower than in the IDA (100.51±5.43 g/l) and ACD groups (103.47±5.54 g/l), whereas the color index level and mean erythrocyte volume were lower in the IDA patients (0.68±0.06; 5.96±0.24 mcm 3 ) than in the ACD (0.92±0.04; 7.73±0.23 mcm 3 ) and COMBI groups (0.72±0.06; 6.38±0.83 mcm 3 ) (Table 1). Additionally, the TIBC in the IDA patients (79.34±3.02 mmol/l) showed a propensity toward increased values compared with the ACD group (52.27±5.36 mmol/l), but no statistically significant differences were noted between the IDA and COMBI (67.34±15.53 mmol/l) patients.…”
Section: Resultsmentioning
confidence: 81%
“…2 In particular, anemic syndrome is a very common manifestation of rheumatoid inflammation. According to literature study by Bloxham et al, 3 anemia develops in 30-70% of patients with RA. Different types of anemia, including iron deficiency anemia (IDA), anemia of chronic disease (ACD), the combination of IDA and ACD (COMBI) anemia, megaloblastic anemia, and hemolytic anemia, have been seen in patients with RA.…”
mentioning
confidence: 99%
“…Stundner et al evaluated 351,103 TKA patients and found a blood transfusion risk approximately 50 % higher for RA patients (23 vs. 17 %; p<0.001) [15]. Anemia of chronic disease, iron deficiency anemia, and bone marrow suppression secondary to medications, which are common findings in patients with RA, are thought to play a role in this increased requirement [16,17]. Similar to the present study, Stundner et al and Elke et al found that the total length of surgical stay was significantly higher in rheumatoid patients (mean of 3.6 vs. 3.5 days, and median of 25 vs. 23 days; p<0.05) [18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 93%
“…3 In particular, anemic syndrome is a very common manifestation of rheumatoid inflammation that could increase RA activity and decrease patient's quality of life. 4 Unfortunately, anemia is not considered a major problem in rheumatoid arthritis RA by the vast majority of physicians. This statement is based on the fact that studies on anemia in RA are sparse, with few systemic reviews, and no extensive literature on its prevalence and effect on various clinical and functional outcomes, including morbidity, mortality, and quality of life.…”
Section: Introductionmentioning
confidence: 99%